Study on the Spatial Variation of Soil Organic Carbon and Its Control Factors in a Typical Karst County - TU Chun; QIN Xingming; LI Fadong; LUO Weiqun (Shuitu Baochi Xuebao, 2025)
[Objective] Exploring the spatial variability of soil organic carbon (SOC) and the differences in its main controlling factors between karst and non-karst areas. [Methods] Taking Wenshan County, a typical karst county in southeast Yunnan Province, as an example, a grid sampling method was employed to conduct the spatial differences in SOC content and storage in top soil (0—20 cm) and deep soil (0—200 cm). Furthermore, we used the semi-variogram function and geographical detector to analyze the impact of external environmental factors on the spatial differentiation of SOC. [Results] The average SOC content in the top soil and deep soil was 17.80 and 5.18 g/kg, respectively, with a total storage of 3 770.89 × 104 t. The distribution pattern revealed higher SOC content in the topsoil of the western region and lower SOC content in the central and northern regions, while the deep soil exhibited higher SOC content in the central and western regions and lower SOC content in the northeastern region in Wenshan County. In non-karst areas, the SOC content in the topsoil and deep soil was 20.88 and 6.12 g/kg, respectively, which was 27.94% and 32.75% higher (p<0.01) than that in karst areas. The semi-variogram model showed that the nugget effect value of SOC ranged from 14.62% to 59.93%, indicating that structural factors dominate the spatial differentiation of SOC in Wenshan County. According to the analysis of the geographical detector, temperature and altitude were the main controlling factors affecting SOC in the top soil layer in karst areas. As the temperature decreased and the altitude increased, the SOC content in Wenshan County showed an increasing trend. However, the SOC content in karst areas was generally lower than that in non-karst areas due to their lower altitudes, severe rocky desertification, and relatively poor vegetation growth. For the deep soil, precipitation was the main controlling factor affecting SOC in karst areas. The leaching effect caused by precipitation might combine dissolved calcium with organic matter to form humic acid calcium, promoting the accumulation of SOC in deep soil. In non-karst areas, stratigraphic chronology played a leading role. The soil developed from Permian basalt parent material may have higher soil clay and macro-aggregate contents, which helps to maintain the physical protection and stability of SOC in deep soil. [Conclusion] This study will provide a reference for precise assessment of SOC and the regulation of soil carbon pools in southwestern karst region.